Depression, anxiety and stress: Analysis of teaching work in universities of Quito - Jirón Jiménez, Jonathan (2024)
The evaluation processes of Ecuadorian universities require that professors must perform three substantive functions during their working day: teaching, research – community outreach, and administrative management. Other research shows that there could be, due to the workload, the appearance of some psychosocial risks such as stress, anxiety and depression. Therefore, the question arises: What are the levels of depression, anxiety and stress present in university teachers in the city of Quito? The methodology used for this study is quantitative, descriptive-correlational in scope, with a non-experimental cross-sectional research design. After applying the Depression, Anxiety and Stress Scale (DASS-21) to 162 professors from public and private universities in the city of Quito, the relevant results were that the academic staff presented 85.2% mild depression, 74.1% mild anxiety and 85.2% mild stress. Regarding the work functions, they perform most frequently, it was found that 51.9% work in the three substantive functions: teaching, research – community outreach and administrative management. It is concluded that there is a significant correlation between the time spent on active breaks and stress and anxiety. These results show the importance of active breaks for professors to minimize psychosocial risks, mainly stress and anxiety.